2021
DOI: 10.1021/acs.langmuir.0c03480
|View full text |Cite
|
Sign up to set email alerts
|

UV-Assisted Li+-Catalyzed Radical Grafting Polymerization of Vinyl Ethers: A New Strategy for Creating Hydrolysis-Resistant and Long-Lived Polymer Brushes as a “Smart” Surface Coating

Abstract: A facile synthetic route was developed to prepare a surface-grafted brush layer of poly­(vinyl ethers) (PVEs) directly by a radical mechanism, with the “naked” Li+ acting as a catalyst. Density functional theory calculations suggested that complexation of naked Li+ to VEs significantly reduced the highest unoccupied molecular orbital–lowest unoccupied molecular orbital (HOMO–LUMO) energy gap from 5.08 to 0.68 eV, providing a better prospect for electron transfer. The structure, morphology, and surface properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…And it could still maintain excellent antibacterial efficiency after being immersed in a highly alkaline environment (0.1 M NaOH aqueous solution) for 3 days. Liao et al 45 grafted hydroxyl vinyl ether monomers onto the surface of the substrate to construct a polymer brush, solving the tension effect of solvents that could result in the destruction of the polymer chain structure and the detachment of the grafting layer from the substrate. It was further demonstrated that under different environmental conditions, the chemical stability of the −C−O−C− species gave the grafting layer significantly high hydrolysis resistance, and there was barely any loss of coordination metal ions and quaternary ammonium salts, thereby ensuring the long-term antibacterial activity of the modified surface.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…And it could still maintain excellent antibacterial efficiency after being immersed in a highly alkaline environment (0.1 M NaOH aqueous solution) for 3 days. Liao et al 45 grafted hydroxyl vinyl ether monomers onto the surface of the substrate to construct a polymer brush, solving the tension effect of solvents that could result in the destruction of the polymer chain structure and the detachment of the grafting layer from the substrate. It was further demonstrated that under different environmental conditions, the chemical stability of the −C−O−C− species gave the grafting layer significantly high hydrolysis resistance, and there was barely any loss of coordination metal ions and quaternary ammonium salts, thereby ensuring the long-term antibacterial activity of the modified surface.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…30,31,37,38 Due to the photosensitivity of ITX, the samples were kept from the light. 45 The mixed solution of BDMT and DEGVE (TTMA and DEGVE for the cross-linked grafting layer) in acetone was dripped onto the clean BOPP-g-ITX surface, and the assembly was irradiated with 365 nm (10,000 mW/cm 2 ) UV light for three times to make sure complete polymerization, depositing grafting polymer layer on the surface of BOPP. The BOPP film might curl up in the heat under a long-time UV light irradiation (there was no cooling of the UV irradiation in our assembly).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After confirming the brush attachment onto Titanium surface, it was important to check the hydrolytic stability of the immobilized brushes at different media. [49,50] Considering their applications in protein patterning, it was decided to use aqueous solvent of varying pH as media. In order to do so, multiple Ti a -g-PPEGMA surfaces having thickness of ≈23 nm was separately immersed for 7 days in three different PBS solutions maintained at pH = 7.4, pH = 5, and pH = 9 and their hydrolytic stability was monitored via thickness measurement by ellipsometry.…”
Section: Modification Of Ti a Surface Via Atom Transfer Radical Polym...mentioning
confidence: 99%
“…Recently, with CH 3 OLi as a complexing agent, we realized the surface graft-polymerization of vinyl ether onto various substrates using benzophenone as a photoinitiator. 42 The grafted poly(vinyl ether) brushes exhibited excellent hydrolysis resistance in both acidic and basic media.…”
Section: Introductionmentioning
confidence: 99%